Contribución a la familia Braconidae (Hymenoptera: Ichneumonoidea) del estado de Aguascalientes - Rodríguez, Julio Cesar; Flores-Dávila, Mariano; Coronado-Blanco, Juana María; García-Martínez, Oswaldo; Aguirre-Uribe, Luis Alberto (Instituto de Ecología, A.C., 2019)
Braconidae is the second most diverse Hymenoptera family in the world, which includes parasitoids of insects and other arthropods. Until 2017, only seven subfamilies, eight genera and four species were known in Aguascalientes. In this research, 608 adults of Braconidae family, corresponding to 18 subfamilies, 44 genera, three species and 107 morphospecies, were obtained in 111 localities of eleven municipalities; from those, 11 subfamilies, 39 genera and three species are new records for the state. This work allowed increasing the registry to 18 subfamilies, 47 genera and seven species of Braconidae for the State of Aguascalientes. Most genera are cosmopolitan, and the species are Nearctic and Neotropical. The most abundant genera were Opius, Aphidius, Trioxys and Aleiodes.